2021
DOI: 10.1093/trstmh/trab126
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of vitamin D and cathelicidin (LL-37) levels between patients with active TB and their healthy contacts in a high HIV prevalence setting: a prospective descriptive study

Abstract: Background Studies from Asia and Europe indicate an association between vitamin D deficiency and susceptibility to TB. We performed an observational case-control study to determine vitamin D and cathelicidin (LL-37) levels and their association with active TB in newly diagnosed and microbiologically confirmed adult TB patients in Zambia, a high HIV prevalence setting. Methods Both total vitamin D and LL-37 were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In healthy volunteers, Bhan et al (2011) [ 9 ] and Dixon et al (2012) [ 10 ] also reported a significant positive correlation but only when serum concentration of 25(OH)D was under the threshold value of 32 ng/ml. In contrast, Stukes et al (2016) and Lungu et al (2021) were unable to confirm the correlation between 25(OH)D and LL-37 circulating levels in a cohort of healthy volunteers [ 7 , 11 ]. The meta-analysis performed by Acen et al (2021) does not have sufficient eligible studies to perform a correlation meta-analysis of vitamin D and LL-37 levels [ 12 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In healthy volunteers, Bhan et al (2011) [ 9 ] and Dixon et al (2012) [ 10 ] also reported a significant positive correlation but only when serum concentration of 25(OH)D was under the threshold value of 32 ng/ml. In contrast, Stukes et al (2016) and Lungu et al (2021) were unable to confirm the correlation between 25(OH)D and LL-37 circulating levels in a cohort of healthy volunteers [ 7 , 11 ]. The meta-analysis performed by Acen et al (2021) does not have sufficient eligible studies to perform a correlation meta-analysis of vitamin D and LL-37 levels [ 12 ].…”
Section: Introductionmentioning
confidence: 96%
“…While a positive correlation between 25(OH)D supplementation and CAMP expression has been established [ 5 ], the link between circulating 25(OH)D and the hCAP18 and/or LL-37 blood peptides remains unclear both in healthy and diseased subjects. In volunteers presenting health issues, Kanda et al (2012) have reported a positive correlation in atopic dermatitis patients as well as Lungu et al (2021) in tuberculosis patients [ 6 , 7 ] contrary to Meca et al (2021) [ 8 ]. In healthy volunteers, Bhan et al (2011) [ 9 ] and Dixon et al (2012) [ 10 ] also reported a significant positive correlation but only when serum concentration of 25(OH)D was under the threshold value of 32 ng/ml.…”
Section: Introductionmentioning
confidence: 99%